2008
DOI: 10.1007/s00198-008-0745-5
|View full text |Cite
|
Sign up to set email alerts
|

Vertebroplasty and kyphoplasty are associated with an increased risk of secondary vertebral compression fractures: a population-based cohort study

Abstract: Introduction Predominantly uncontrolled studies suggest that there may be a greater risk of subsequent vertebral compression fractures (VCFs) associated with vertebroplasty and kyphoplasty. To further understand the risk of VCFs, we conducted a population-based retrospective cohort study using data from a large regional health insurer. Materials and Methods Administrative claims procedure codes were used to identify a treatment group of patients receiving either a vertebroplasty or kyphoplasty (treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 28 publications
2
74
1
1
Order By: Relevance
“…Some noncontrolled follow-up studies after PV reported that new VCFs, more often located adjacent to the vertebroplasty level, allegedly contributed to the increased dimensional stability of the cemented vertebral body. 6,8,22,23 However, in our randomized study, no difference in location distribution of new VCFs was found after PV and conservative therapy. In addition, after PV, the risk for a new VCF adjacent to the cemented level was equal to the risk of a new VCF at a distant level.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Some noncontrolled follow-up studies after PV reported that new VCFs, more often located adjacent to the vertebroplasty level, allegedly contributed to the increased dimensional stability of the cemented vertebral body. 6,8,22,23 However, in our randomized study, no difference in location distribution of new VCFs was found after PV and conservative therapy. In addition, after PV, the risk for a new VCF adjacent to the cemented level was equal to the risk of a new VCF at a distant level.…”
Section: Discussionmentioning
confidence: 47%
“…[9][10][11][12][13]20 On the other hand, some studies have reported an increased risk of new VCFs after PV. 5,6,8,20,21 However, most of these studies were small nonrandomized follow-up only studies, lacking a control group without intervention. Some noncontrolled follow-up studies after PV reported that new VCFs, more often located adjacent to the vertebroplasty level, allegedly contributed to the increased dimensional stability of the cemented vertebral body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disadvantage has been surmounted by using previously described surrogate measures of functional outcome including in-hospital complications [3,5,10,11,33,52,53], in-hospital mortality [1,3,10,33,53], and patient disposition at hospital discharge [10,11,33,52,53]. Third, evidence is mounting to suggest patients who undergo kyphoplasty experience up to 36% higher risk of subsequent VCF resulting from the increased biomechanical stiffness of the treated vertebral body [22,29,45]. The NIS database contains the information pertaining to a specific hospitalization for a given patient whose identification has been removed from the record.…”
Section: Discussionmentioning
confidence: 99%
“…New osteoporotic vertebral compression fractures, in the months after VP, are reported in 7-63 % of VP patients, up to 82 % of these occur at the adjacent levels, with adjacent fractures occurring sooner than nonadjacent fractures; rates of recurrent fracture of the augmented vertebra itself range up to 63 % in the literature [1,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It is still under debate whether new vertebral fractures appear more often in patients who received cement augmentation than in conservatively treated patients; some studies support this hypothesis [1,6,7,[27][28][29], while others question it [2,3,26,30]. Reducing the augmentation volume [31], using low-modulus PMMA [32] and prophylactic augmentation of adjacent vertebrae [13,25,33] have been proposed as ways of minimizing the risk of subsequent fractures.…”
Section: Introductionmentioning
confidence: 99%